2011
DOI: 10.1242/jeb.051839
|View full text |Cite
|
Sign up to set email alerts
|

Differential muscular myosin heavy chain expression of the pectoral and pelvic girdles during early growth in the king penguin (Aptenodytes patagonicus) chick

Abstract: SUMMARYContinuous growth, associated with a steady parental food supply, is a general pattern in offspring development. So that young chicks can acquire their locomotor independence, this period is usually marked by a fast maturation of muscles, during which different myosin heavy chain (MyHC) isoforms are expressed. However, parental food provisioning may fluctuate seasonally, and offspring therefore face a challenge to ensure the necessary maturation of their tissues when energy is limited. To address this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…; Erbrech et al . ). In the present study, we detected the presence of a slow fibre population that has not been observed in other Sphenisciformes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Erbrech et al . ). In the present study, we detected the presence of a slow fibre population that has not been observed in other Sphenisciformes.…”
Section: Discussionmentioning
confidence: 97%
“…; Erbrech et al . ), it is possible that only superficial muscle was sampled, accounting for the lack of slow fibres. As many experiments use biopsy samples from the pectoralis and supracoracoideus (Williams et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation